Management of neuroendocrine tumors of the pancreas and digestive tract : from surgery to targeted therapies: a multidisciplinary approach - Raymond, Eric; Faivre, Sandrine; Ruszniewski, Philippe; Raymond, Eric (Springer Paris, 2014)
This book pursues a multidisciplinary approach, presenting chapters with updated information on various aspects of treatment for patients with neuroendocrine tumors. Authors have been selected from expert centers in Europe and the United States. The goal of this book is to comprehensively summarize recent data and provide inspiring ideas to optimize the care of patients with neuroendocrine tumors.   Neuroendocrine tumors are fascinating multifaceted diseases that can primarily localize in many organs with various presentations. These tumors are rare but their increasing incidence renders likely that physicians caring for cancers may have either already faced or may be certainly exposed to diagnose and/or treat a patient with neuroendocrine tumors. Over the last years, novel therapeutic options have emerged for neuroendocrine tumors, profoundly challenging practices that had previously been the standards for decades. These include - but are not limited to - somatostatin analogues, targeted therapies such as tyrosine kinase and mTOR inhibitors, antiangiogenic compounds, but also peptide-receptor targeted therapy or radioembolization. This changing field has generated novel treatment algorithms to guide medical decisions. To better understand and handle the multidisciplinary approaches that are required for optimizing the care of neuroendocrine tumor patients, physicians are now looking for references from experts and comprehensive reviews summarizing current knowledge on treatments for patients with neuroendocrine tumors.